Rewired Downregulation of DNA Gyrase Impacts Cell Division, Expression of Topology Modulators, and Transcription in Mycobacterium smegmatis. Issue 24 (7th December 2018) - Guha, Sarmistha; Udupa, Shubha; Ahmed, Wareed; Nagaraja, Valakunja
Abstract: DNA gyrase, essential for DNA replication and transcription, has traditionally been studied in vivo by treatments that inhibit the enzyme activity. Due to its indispensable function, gyrA and gyrB deletions cannot be generated. The coumarin inhibitors of gyrase induce the supercoiling-sensitive gyrase promoter by a mechanism termed relaxation-stimulated transcription. Hence, to study the effect of sustained reduction in gyrase levels, a conditional-knockdown strain was generated in Mycobacterium smegmatis such that gyrase expression was controlled by a supercoiling non-responsive regulatory circuit. Decreasing intracellular gyrase protein levels beyond 50% affected cell growth. Reduced gyrase levels in the reprogrammed gyr operon caused chromosome relaxation, diffuse nucleoid structure, cell elongation, and altered gene expression. The key cell division protein, ftsZ, was severely reduced in the elongated cells, indicating a link between gyrase and cell division. Low levels of gyrase resulted in low compensatory expression of topoisomerase I and elevated expression of topology modulators hupB and lsr2 . Altered supercoiling due to gyrase depletion caused corresponding changes in the RNA polymerase density on transcription units leading to their altered transcription. The enhanced susceptibility of the knockdown strain to anti-tubercular drugs suggests its utility for screening new molecules that may act synergistically with gyrase inhibitors. Graphical Abstract: Highlights: DNA gyrase levels are restored by relaxation-stimulated transcription. Replacing native Pgyr promoter with supercoiling-insensitive promoter ensures continuous gyrase repression. A minimum threshold of gyrase is required for the organism's survival. Gyrase depletion alters cell morphology, growth, and drug susceptibility. Reduced gyrase level alters RNA polymerase occupancy and transcription.